2014
DOI: 10.14740/cr359w
|View full text |Cite
|
Sign up to set email alerts
|

3-Methylglutaconyl-Coenzyme-A Hydratase Deficiency and the Development of Dilated Cardiomyopathy

Abstract: A 25-year-old Canadian male with a history of 3-methylglutaconyl-coenzyme-A hydratase deficiency, also known as 3-methylglutaconic aciduria type I, a very rare inborn error of metabolism, presented with respiratory distress, nausea, vomiting and signs of multisystem organ failure due to a suspected underlying infectious process. An electrocardiogram revealed bilateral atrial enlargement and an elevated brain natriuretic peptide on the initial laboratory studies, which prompted a more thorough cardiac workup. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…32,33 A study on 3-methylglutaconic aciduria (3-MGA) also revealed the progression of cardiomyopathy in OAs. 34 Furthermore, in MMA patients, major secondary complications include intellectual impairment, tubulointerstitial nephritis with progressive renal failure, metabolic stroke, which referes to acute and chronic basal ganglia injury, pancreatitis, growth failure, functional immune impairment, and optic nerve atrophy. 35 Late-onset forms of OAs are less frequent, and these are characterised by recurrent life-threatening episodes of metabolic crises characterised by encephalopathy, vomiting and dehydration.…”
Section: Removal Of the Toxinsmentioning
confidence: 99%
“…32,33 A study on 3-methylglutaconic aciduria (3-MGA) also revealed the progression of cardiomyopathy in OAs. 34 Furthermore, in MMA patients, major secondary complications include intellectual impairment, tubulointerstitial nephritis with progressive renal failure, metabolic stroke, which referes to acute and chronic basal ganglia injury, pancreatitis, growth failure, functional immune impairment, and optic nerve atrophy. 35 Late-onset forms of OAs are less frequent, and these are characterised by recurrent life-threatening episodes of metabolic crises characterised by encephalopathy, vomiting and dehydration.…”
Section: Removal Of the Toxinsmentioning
confidence: 99%
“…12 Type I: A rare AR condition caused by 3-methylglutaconyl-CoA hydratase deficiency. 123 This enzyme converts 3-methylglutaconyl-CoA to 3-hydroxy-3-methylglutaryl-CoA, which is essential in leucine degradation. These patients show high levels of 3-methylglutaconic acid, 3-methyl glutaric acid, and 3-hydroxyisovaleric acid in urine.…”
Section: Prognosismentioning
confidence: 99%
“…Patients affected by this disease manifest a wide range of clinical signs, ranging from no or mild symptoms [8,9] to mild neurological impairment [10,11], acute encephalopathy [12][13][14], severe encephalopathy with basal ganglia involvement [15,16], and slowly progressive leukoencephalopathy presenting in adulthood [17][18][19][20]. Dilated cardiomyopathy [21], central precocious puberty, attention deficient hyperactivity disorder, learning disability, and white matter alterations on magnetic resonance imaging [22] have also been described.…”
Section: Introductionmentioning
confidence: 99%